Sejarah Perkembangan Asuransi Syariah Serta Perbedaannya Dengan Asuransi Konvensional di Indonesia - Maura Syafa’ah, Della; Muhammad Muchlis, Madian (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
One example of teachings related to commands and prohibitions is insurance. Insurance is an attempt to protect each other in a number of people. Insurance that is often used by most people today is conventional insurance. This type of insurance is not insurance known by the previous figures, namely among fiqh experts. Because conventional insurance mechanisms are not included in transactions known by Islamic fiqh. Thus, this study aims to determine the extent of the development of Islamic insurance by looking at the difference with conventional insurance. In this study, the authors used a qualitative research approach in the form of literature studies. Data collection based on relevant reference sources. The data sources taken are secondary data in the form of articles and journals as well as information on the internet based on the object of discussion and primary data in the form of laws or sources that are accounted for. The result of this study is a good development of Sharia insurance in Indonesia and Sharia insurance has differences with conventional insurance that is the basic concept, risk management, and other principles. The increased appreciation of the surrounding community to this insurance, it will experience rapid growth in both Sharia insurance and conventional insurance in the future.